Whey valorization for sustainable polyhydroxyalkanoate production by Bacillus megaterium: Production, characterization and in vitro biocompatibility evaluation. (1st February 2020) - Israni, Neetu; Venkatachalam, Prerana; Gajaraj, Bharath; Varalakshmi, Kilingar Nadumane; Shivakumar, Srividya
Abstract: Polyhydroxyalkanoates (PHAs) are biodegradable biopolymers acclaimed as an eco-friendly substitute of hazardously polluting petrochemical plastics. Using industrial by-products as PHA feedstocks could improve its process economics and market implementation. Valorizing the plenteous, nutritive pollutant whey as PHA production feedstock would be an excellent whey management strategy. This study aimed at whole/crude whey valorization for value-added PHA production using B. megaterium Ti3 innate protease, alleviating pretreatments. Response surface methodology (RSM) media optimization ascertained whey (%) as the key influential factor ( p  < 0.05). The optimized and validated RSM model (R 2, 0.991; desirability, 1) facilitated 12.2, 11.5 folds increased PHA yield (2.20 ± 0.11 g/L) and productivity (0.05 gPHA/L/h). A positive correlation (r 2, 0.95 and 0.87) was observed amid the innate enzymes (protease and lipase) and PHA production. The PHA was characterized by 1 H and 13 C NMR, GPC, TGA, and was identified as poly (3-hydroxybutyrate) (P3HB) by NMR. A significantly reduced roughness (110 ± 5.6 nm); increased hydrophilicity (8.6 ± 0.3 and 8.7 ± 0.5%), protein adsorption (68.75 ± 2.55 μg/cm 2 ) and 1.6 folds higher biocompatibility achieved on poly (ethylene glycol) (PEG) blending compared to neat P3HB films. This is the first report on B. megaterium innate enzyme based whey valorization to PHAs also demonstrating its biomedical applicability. Graphical abstract: Image 1 Highlights: Whole/Crude whey valorization to P3HB by β‒galactosidase negative B. megaterium. High P3HB productivity by innate protease and lipase excluded whey pretreatment. P3HB showed higher thermal stability on thermogravimetric analysis. Notably improved in vitro biocompatibility by poly (ethylene glycol) blending. First in vitro applicability demonstration of dairy waste whey sourced P3HB.